2018
DOI: 10.3389/fmicb.2018.03169
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bacterial Communities Mediating the Treatment of an As-Rich Acid Mine Drainage in a Field Pilot

Abstract: Passive treatment based on iron biological oxidation is a promising strategy for Arsenic (As)-rich acid mine drainage (AMD) remediation. In the present study, we characterized by 16S rRNA metabarcoding the bacterial diversity in a field-pilot bioreactor treating extremely As-rich AMD in situ, over a 6 months monitoring period. Inside the bioreactor, the bacterial communities responsible for iron and arsenic removal formed a biofilm (“biogenic precipitate”) whose composition varied in time and space. These comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 83 publications
(150 reference statements)
1
10
0
Order By: Relevance
“…Passive treatment of As-rich AMD via iron biological oxidation showed that the biogenic precipitate formed is dominated by iron-oxidizing bacteria (FeOB) such as Gallionella, Ferrovum, Leptospirillum, Acidithiobacillus, and Ferritrophicum, and arsenite-oxidizing Thiomonas spp. (Laroche et al, 2018). Similarly, passive bioremediation system enriched with Ignavibacterium, Pelotomaculum, and Petrimonas and species known to catalyse the dissimilatory reduction of ferric iron (Geobacter psychrophilus), oxidation of sulfur (Polaromonas hydrogenivorans, Flavobacterium johnsoniae, Dechloromonas aromatica, Novosphingobium sediminicola, Clostridium saccharobutylicum, and Pseudomonas extremaustralis), and reduction of nitrate (Sulfuricella denitrificans, A. ferrooxidans, and Acidithiobacillus thiooxidans), methylotrophs (methane/methanol-oxidizers), and anaerobic aromatic compound-degraders (Syntrophorhabdus sp.)…”
Section: Amd Remediation Technologies and Microbial Community Structurementioning
confidence: 99%
“…Passive treatment of As-rich AMD via iron biological oxidation showed that the biogenic precipitate formed is dominated by iron-oxidizing bacteria (FeOB) such as Gallionella, Ferrovum, Leptospirillum, Acidithiobacillus, and Ferritrophicum, and arsenite-oxidizing Thiomonas spp. (Laroche et al, 2018). Similarly, passive bioremediation system enriched with Ignavibacterium, Pelotomaculum, and Petrimonas and species known to catalyse the dissimilatory reduction of ferric iron (Geobacter psychrophilus), oxidation of sulfur (Polaromonas hydrogenivorans, Flavobacterium johnsoniae, Dechloromonas aromatica, Novosphingobium sediminicola, Clostridium saccharobutylicum, and Pseudomonas extremaustralis), and reduction of nitrate (Sulfuricella denitrificans, A. ferrooxidans, and Acidithiobacillus thiooxidans), methylotrophs (methane/methanol-oxidizers), and anaerobic aromatic compound-degraders (Syntrophorhabdus sp.)…”
Section: Amd Remediation Technologies and Microbial Community Structurementioning
confidence: 99%
“…In the low pH FeOX reactors examined in this study, geochemical conditions and temporal distances influenced microbial community composition without affecting Fe(II) oxidation rates (Sheng et al ., 2016; Sheng et al ., 2017), which may be imparted by the presence of multiple FeOX taxa that were able to co‐exist. These results are consistent with previous studies, which showed that microbial communities in flow‐through Fe(II)‐oxidizing reactors changed over time without affecting reactor performance (Jones and Johnson, 2016; Laroche et al ., 2018). Metabolic potential for Fe(II) oxidation at low pH could derive from a variety of populations including Acidithiobacillus sp., Ferrovum sp.…”
Section: Resultsmentioning
confidence: 99%
“…Fe oxide precipitates have been shown to scavenge arsenic from AMD in passive treatment systems (Elbaz-Poulichet et al, 2006;Fernandez-Rojo et al, 2019;Valente et al, 2011). Analysis of the oxide precipitates identified that Fe(II) oxidising bacteria dominated and known arsenite oxidisers were also present, therefore microbes were likely contributing to As removal from solution (Laroche et al, 2018). The release of 25,000 -50,000 m 3 of acidic mine water from the Wheal Jane mine to the Fal River estuary (Cornwall, England) over 24 h in 1992 induced the Government to investigate remediation options (pumping 90 -300 L s -1 ) (Younger et al, 2005).…”
Section: Accepted Articlementioning
confidence: 99%